FuzzyLogicAppliedTo Intelligent Traffic Light - Endyk Noviyantono; . Muhammad (International Conference on Engineering and Technology Development (ICETD), 2012)
Traffic congestion is an obstacle in the big cities. Traffic light as a way of the traffic regulation to be a solution right now. With the installation of digital numbers as a counter in the lane of traffic light that can give time to continue to move to indicate the length of the queues turn at the intersection, is currently widely used on path scrossing, or intersection of roads in Indonesia. However, for a continuous density in traffic, can increases the counte rof traffic light at any time, should always be arranged, thereâs so incovenience to the rider.This research is a about development called intelligent traffic light that is able toadapt wellto the congestion that occurs inthe traffic lane controlled byt raffic lights. By utilizing ATMega AVR-32 on electrical hardware development which will be applied to simulated traffic light and with the use of digital cameras that observ ethe density of the lane,would bea complete automation solution for paths run properly. Fuzzy algorithms will calculate carefully based on the information transmitted by the camera into microcontroller, then processed and rendered a decision which path in the lane is allowed to be run. High-density or Low-density in the lane of roads, will be important information for the fuzzy logic to determine whether the decision to. Finally, with these applied hardware and the implementation of fuzzy algorithms will be handled traffic on the lane intelligently.